Framing the “Ponzi Scheme” Allegation in Indonesia’s Hajj Fund Management: A Comparative News Media Analysis - Nurul Qoyimah; Ana Nadhya Abrar; Nyarwi Ahmad (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2026)
This article examines how Indonesian news media construct the “Ponzi Scheme” allegation in the controversy over Hajj fund management. Although Hajj financing has been widely discussed in legal, administrative, and Islamic economic studies, limited attention has been given to how mainstream news media frame the issue as a matter of public meaning, religious legitimacy, and financial governance. Using Robert M. Entman’s four-function framing model, this study analyzes six news articles from Republika, Antara News Agency, and Tempo published between 2023 and 2024. The findings show that the media frame the issue through three dominant frames: financial sustainability, religious-ethical legitimacy, and governance accountability. Republika emphasizes religious and ethical concerns, Antara foregrounds institutional assurance and administrative rationality, while Tempo highlights structural risks and moral urgency. The study contributes to communication scholarship by showing how a financial policy controversy is transformed into a moralized public discourse through media framing and metaphorical construction. It also underscores the importance of transparent, consistent, and accessible public communication in managing religious financial governance.